Irreconcilable Differences? Tourette Syndrome, Disability, and Definition in Democratic Policy Debates - Sara Newman (Disability Studies Quarterly, 2009)
This paper examines a recent policy debate by means of a particular rhetorical approach. That approach, based on the strategic use of word definitions and repetition, is applied to the deliberative process underlying attempts to provide appropriate special education accommodations for students with Tourette Syndrome (TS) in the U.S. public school system. Thus, this paper’s goals are threefold: to present and apply an explicit model for arguing and advocating with definitions; to examine how an advocacy organization has participated in civic deliberations about disability law in the public schools; and to offer this approach as a model for future advocacy work.